PEMBERDAYAAN PEMUDA MAJELIS AL BAROYA SEBAGAI KADER PECINTA SHOLAWAT - Qhusyaeri, Ahmad; Taufiqurrohman, Achmad; Shiolihin, M.; Prasetiya, Benny (LPPM STAI Muhammadiyah Probolinggo, 2024)
In this millennial era, the role of the younger generation is very important in driving change that improves the quality of a nation. One of the religious activities that is popular nowadays and has the potential to empower youth is the Sholawat Assembly. This research uses a community service method with a qualitative descriptive approach, involving participation from all parties to jointly identify and handle existing problems. This research focuses on empowering the youth of the Al Baroya Council in instilling a love of prayer. The research location was carried out at the Nurul Anwar Mosque, Pohsangit Kidul. Data collection methods involve consultation, direct observation, and data analysis. The main aim of this research is to revive the enthusiasm of youth and local communities in prayer and religious activities. Based on the results of interviews and research observations, it appears that evaluation and analysis are a strong basis for developing youth empowerment programs in the future. Empowering the youth of the Al Baroya Council as a generation of prayer lovers is an important step in strengthening religious identity in society. Through empowerment, the youth of the Al Baroya Council are actively involved in religious activities aimed at increasing solidarity, togetherness and spirituality.